P117 THE IMPACT OF ELDERLY ON SURGICAL OUTCOMES AFTER IVOR-LEWIS ESOPHAGECTOMY: REVIEW OF A SINGLE INSTITUTION EXPERIENCE. (23rd November 2019) - Cossu, A; Parise, P; Puccetti, F; Palucci, M; Cerchione, R; Elmore, U; Rosati, R
Abstract: Background: Esophagectomy is a surgical procedure burdened by a high morbidity rate. The effect of minimally invasive (MI) approach on elderly patients is still not clear. Aim of this study was to analyze the impact of MI approach on post-operative course according to the patient age. Methods: A consecutive series of 692 patients underwent to elective oncological esophagectomy between 1997 and 2017. All data were entered into a prospective database. Patients submitted to 3-flield or trans-hiatal esophagectomy were excluded and only Ivor-Lewis open, hybrid or totally minimally invasive esophagectomy were evaluated. Patients were stratified according to age in 3 groups: Group A (≤ 50 years) 53 patients, Group B (> 51 and < 70 years) 269 and Group C (were ≥71 years) 126. Clinical and pathological factors influencing surgical outcome were evaluated. Complications were classified according to Clavien-Dindo (CD). Results: As expected outcomes worsened with patients age (CD ≥ 3b: 7.5% group A, 13% group B and 21% group C. p=0.001), mortality (0% group A, 3% group B and 5.5% group C. p=0.035) and length of stay (10 days group A, 11 days group B and 13 days group C. p=0.001). A statistically significant higher incidence of anastomostic leaks was observed among patients submitted to totally MI esophagectomy in group C vs A and B that were respectively 12, 5%, 0% and 7%. Major respiratory complications were not statistically different among these 3 three sub-group. Conclusions: Old age has a significant impact on outcomes after esophagectomy. In this subset of patients a MI approach could also increase postoperative morbidity. Elderly patients should be carefully selected before to be submitted to MI esophagectomy.